If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3(9a+6)=-7
We move all terms to the left:
1/3(9a+6)-(-7)=0
Domain of the equation: 3(9a+6)!=0We add all the numbers together, and all the variables
a∈R
1/3(9a+6)+7=0
We multiply all the terms by the denominator
7*3(9a+6)+1=0
Wy multiply elements
21a(9+1=0
| 3c+4=12+10. | | x+2=-2x+11 | | (3-x)/(1-2x)=5 | | 1/6(2x+2)=1/3 | | 6^m+3=36 | | 3^3r+1=81 | | (x-12)^2=27 | | 10^4=(x^2+1) | | 2^-x-2=2^6 | | X+(0.06xX)=5 | | 5^-2m=5^3m | | 3(v+7)÷-3=7(v-1)÷-9 | | x^2+13x-7=15 | | x/4=6/10 | | 6y=3×,y=1/2× | | 3^-3n=9 | | t^2-t-3/2=0 | | 6x-52=4x+46 | | 23+4m=÷2 | | 2.7(n+7.8)+6.5=9n-4 | | p2-33p+16=0 | | n+(n+40)+(n-30)=150 | | 2m/5+7/10=9/2 | | 6(y+7.7)-8y=-9 | | x*x*x+2x=26 | | 2x+1=7,x= | | -2x+7x=x | | 9(c+9.6)+6=5.2c+1.5 | | 9x-5(2x-9)=2(x-1)+9 | | 2(y+7)=5y-1 | | (3x)(-5x)=-2x | | 6x+(2x*2(2x*2-1)+(3x*2-1+2x)-2x+1)+2x-1=3 |